The Future Ground of Organizations on the Awareness and Diversity of Knowledge: Innovation - Yalçın Yalçınkaya (Türk Kütüphaneciliği)
Innovation is described as well as the concept of a process (to refresh / renewal) and a result (innovation). Although very different definitions, innovation means; converting knowledge, a new application or new ideas to a new product or service. Especially, knowledge is a people-focused concept and has more details for people who work in organizations. This awareness can be useful for predicting and planning the future for organizations. The diversity of knowledge, which brings out the importance of the organization and will provide knowledge-based innovation, improves solutions against organizational problems, provides a competitive advantage and develops what the organization needs. The methodology of this study is basically descriptive and theoretical. In this study, the main findings of the literature regarding these two subjects (knowledge management – innovation) are evaluated and a conceptual framework for further research is offered. The purpose of this study is to determine the intersection points of the literatures both of knowledge management and innovation. This will present a functional perspective to the researchers, the executives and the operators.